Neurological and immunological characteristics of a novel immortalized bovine brainstem-derived cell line and its susceptibility to arbovirus infection - Ikeda, Rina; Yanase, Tohru; Konishi, Misako; Murota, Katsunori; Tanaka, Shogo; Takenouchi, Takato (Frontiers in Cellular and Infection Microbiology, 2025)
Immortalized bovine neuronal cell lines provide a reliable in vitro model for studying interactions with bovine infectious pathogens that target the host nervous system. Although we previously established an immortalized fetal bovine brain-derived FBBC-1 cell line, there are currently no other bovine neuronal cell lines commonly available. In the present study, we developed a novel immortalized cell line, IKBM, derived from the adult bovine brainstem by transferring a SV40 large T antigen gene using lentiviral vectors, and compared its characteristics to the FBBC-1 cell line. As with FBBC-1 cells, IKBM cells extended neurite-like processes in response to agents that increase cytosolic cyclic AMP levels. A comprehensive analysis using RNA sequencing demonstrated that both cell lines potentially possess neural progenitor cell-like properties and differentiate into dopaminergic neuron-like cells after induction of the outgrowth of neurite-like processes. Unexpectedly, we found that the mRNAs of multiple immunomodulatory molecules were highly expressed in IKBM cells, but not in FBBC-1 cells. Although IKBM cells were susceptible to infection with arboviruses (Akabane and Chuzan viruses) that cause neurological symptoms in cattle, viral titers were lower in IKBM cell cultures than in hamster lung-derived HmLu-1 cell cultures, which are frequently used to isolate arboviruses. The reduced production of viruses in IKBM cell cultures may be related to the high expression of immunomodulatory molecules in these cells. Therefore, IKBM and FBBC-1 cell lines offer the opportunity to develop unique in vitro models of the bovine nervous system for the study of host-pathogen interactions based on their respective properties.